2008
DOI: 10.1158/1535-7163.mct-08-0195
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer steroid sulfatase inhibitors: synthesis of a potent fluorinated second-generation agent, in vitro and in vivo activities, molecular modeling, and protein crystallography

Abstract: An improved steroid sulfatase inhibitor was prepared by replacing the N-propyl group of the second-generation steroid-like inhibitor (2) with a N-3,3,3-trifluoropropyl group to give (10). This compound is 5-fold more potent in vitro, completely inhibits rat liver steroid sulfatase activity after a single oral dose of 0.5 mg/kg, and exhibits a significantly longer duration of inhibition over (2). These biological properties are attributed to the increased lipophilicity and metabolic stability of (10) rendered b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Crystal structure of hCA II in complex with compound 3 was determined at 1.80 Å resolution, revealing a clear electron density for the inhibitor molecule in the enzyme active site (Figure 2 [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] , compound 1 interacts directly with the zinc ion of the active site, with its sulphamate nitrogen atom N1 (for atom numbering see Figure 1) displacing the water molecule/hydroxide ion, which in the not-inhibited enzyme occupies the fourth coordination position. Additional hydrogen bonds between the sulphamate moiety and residues within the enzyme active site contribute to stabilise the binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structure of hCA II in complex with compound 3 was determined at 1.80 Å resolution, revealing a clear electron density for the inhibitor molecule in the enzyme active site (Figure 2 [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] , compound 1 interacts directly with the zinc ion of the active site, with its sulphamate nitrogen atom N1 (for atom numbering see Figure 1) displacing the water molecule/hydroxide ion, which in the not-inhibited enzyme occupies the fourth coordination position. Additional hydrogen bonds between the sulphamate moiety and residues within the enzyme active site contribute to stabilise the binding.…”
Section: Resultsmentioning
confidence: 99%
“…To understand if the different position assumed by N2 and O3 atoms in the enzyme active site was associated to a peculiarity of the two complexes under investigation, or to a more general behaviour of sulphamate and sulphamide derivatives, a comparative analysis of all hCA II/sulphamate and hCA II/sulphamide structures available in the PDB was undertaken 25,26,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][67][68][69][70][71] . Surprisingly, the analysis of all these structures revealed that, independently of the nature of the moiety attached to the ZBG, the distance between the Thr200OG1 atom and the sulphamide nitrogen N2 in hCA II/sulphamide complexes was generally shorter than the corresponding distance between the sulphamate oxygen O3 and the same enzyme atom in hCA II/sulphamate complexes (see Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…The STS inhibitors presented in Table 1 (optimized at above describe three levels of theory: (i) MM+, (ii) PM7 and (iii) DFT B3LYP 6-31++G*) were analysed in order to select compounds structurally similar to 667-COUMATE that was thoroughly studied according to mode of inhibitor binding to STS [34]. Hierarchical cluster analysis (HCA) with Euclidian distances and Ward's method of linkage [34] was applied.…”
Section: Ligand Preparationmentioning
confidence: 99%
“…Hierarchical cluster analysis (HCA) with Euclidian distances and Ward's method of linkage [34] was applied. Selected inhibitors were saved as PDB file format for input to PatchDock software [35].…”
Section: Ligand Preparationmentioning
confidence: 99%
See 1 more Smart Citation